2022
DOI: 10.1002/ueg2.12301
|View full text |Cite
|
Sign up to set email alerts
|

Liver and spleen volumes are associated with prognosis of compensated and decompensated cirrhosis and parallel its natural history

Abstract: Objective Cirrhosis is characterized by the complex interplay among biological, histological and haemodynamic events. Liver and spleen remodelling occur throughout its natural history, but the prognostic role of these volumetric changes is unclear. We evaluated the relationship between volumetric changes assessed by multidetector computerised tomography (MDCT) and landmark features of cirrhosis. Methods We included consecutive cirrhotic patients who underwent liver transplantation (LT) or hepatocellular carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“… 13 , 14 Moreover, a recent study has shown that the increase in LSVR during the compensated phase of cirrhosis is associated with CSPH, while the decrease in total liver volume (LV) and liver/spleen volume ratio (LV/SV) are associated with clinical decompensation. 19 Therefore, liver and spleen volumetry may represent a novel approach to the non-invasive diagnosis of CSPH, but its role in this setting is still to be fully defined. We hypothesized that liver and spleen volumes may predict CSPH in patients with compensated cirrhosis and HCC.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Moreover, a recent study has shown that the increase in LSVR during the compensated phase of cirrhosis is associated with CSPH, while the decrease in total liver volume (LV) and liver/spleen volume ratio (LV/SV) are associated with clinical decompensation. 19 Therefore, liver and spleen volumetry may represent a novel approach to the non-invasive diagnosis of CSPH, but its role in this setting is still to be fully defined. We hypothesized that liver and spleen volumes may predict CSPH in patients with compensated cirrhosis and HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in other studies analyzed in previous studies of liver brosis and cirrhosis, liver volume (LV) had been positively correlated with height, and the mean caudate lobe volume in patients with Child-Pugh class A was 36.83 +/-22.11 cm3, which was signi cantly greater than the values in patients with Child-Pugh class B and C 31 . Patients with liver brosis and cirrhosis had signi cantly reduced the liver volume 32,33 . However, there are relatively few studies in healthy populations with susceptibility to progressive liver brosis, or even cirrhosis as observational studies, even when confounding factors are taken into account, may be subject to biases that undermine validity (e.g., residual confounding).…”
Section: Discussionmentioning
confidence: 99%
“…
Can we predict the future of patients with liver cirrhosis using volumetrics?In the article on computed tomography (CT) volumetrics in liver cirrhosis Romero-Cristóbal et al investigated the relationship between changes in liver-spleen volume and features of cirrhosis in patients with compensated or decompensated liver cirrhosis who either underwent liver transplantation or partial hepatectomy for hepatocellular carcinoma (HCC). 1 The authors showed in this Spanish cross-sectional single center study that changes in liver volume, liver segmental volume ratio and liver-spleen volume ratio evaluated by CT reflected the course of disease progression through the different stages of liver cirrhosis. Specific changes in volumetrics appeared to be related to compensated cirrhosis, compensated cirrhosis with development of portal hypertension and decompensated liver cirrhosis.
…”
mentioning
confidence: 90%
“…In the article on computed tomography (CT) volumetrics in liver cirrhosis Romero‐Cristóbal et al. investigated the relationship between changes in liver‐spleen volume and features of cirrhosis in patients with compensated or decompensated liver cirrhosis who either underwent liver transplantation or partial hepatectomy for hepatocellular carcinoma (HCC) 1 …”
mentioning
confidence: 99%